Hard rain [large type] - Daniels, B. J. (Daniels, B. J. Montana Hamiltons., 2017)
"When Brody McTavish and Harper Hamilton discover human remains uncovered by a recent rainstorm, family secrets comes to light that may destroy their chance at love. As they seek to uncover the truth of the long-ago murder, their lives are threatened by an enemy intent on keeping the past buried."--